Bmi1+ Progenitor Cell Dynamics in Murine Cornea During Homeostasis and Wound Healing. (17th January 2018) - Kalha, Solja; Shrestha, Bideep; Sanz Navarro, Maria; Jones, Kyle B.; Klein, Ophir D.; Michon, Frederic
Abstract : The outermost layer of the eye, the cornea, is renewed continuously throughout life. Stem cells of the corneal epithelium reside in the limbus at the corneal periphery and ensure homeostasis of the central epithelium. However, in young mice, homeostasis relies on cells located in the basal layer of the central corneal epithelium. Here, we first studied corneal growth during the transition from newborn to adult and assessed Keratin 19 ( Krt19 ) expression as a hallmark of corneal maturation. Next, we set out to identify a novel marker of murine corneal epithelial progenitor cells before, during and after maturation, and we found that Bmi1 is expressed in the basal epithelium of the central cornea and limbus. Furthermore, we demonstrated that Bmi1+ cells participated in tissue replenishment in the central cornea. These Bmi1+ cells did not maintain homeostasis of the cornea for more than 3 months, reflecting their status as progenitor rather than stem cells. Finally, after injury, Bmi1+ cells fueled homeostatic maintenance, whereas wound closure occurred via epithelial reorganization. Abstract : Corneal renewal is a dynamic process. Basally located central epithelial progenitor cells maintain the corneal layers for a limited time, whereas stem cells reside in the limbus. Healing after injury occurs via reorganization of the epithelium.